Endoscopic View of the Aorta Through the Oesophagus: An Unusual Complication Post Thoracic Endovascular Aortic Repair - Kushedison Yunus; Hasib Ahmadzai; Eleanor Noreen Dunlop; Andrew Thomson (Case Reports in Gastrointestinal Medicine)
We present a case of an 80-year-old female who presented with chest pain, vomiting and night sweats a few weeks post thoracic endovascular aortic aneurysm repair (TEVAR). A computed tomography (CT) scan demonstrated a type 1B endoleak for which she underwent a repeat TEVAR. Postoperatively, she developed fever, dysphagia, haematemesis and melaena. CT angiography subsequently confirmed an aorto-oesophageal fistula (AEF). Gastroscopy was performed to confirm this and found an ovoid oesophageal perforation with visible aortic graft and purulent fluid. Serial endoscopic oesophageal stents were placed and the patient recovered after an oesophageal Ultraflex stent was placed. Unfortunately, however, the patient was found unresponsive at home with black vomitus and in cardiac arrest and passed away 18 months after her initial endoscopic procedure. This case highlights that AEF is a complication following a TEVAR procedure. This can be managed temporarily with oesophageal stent placement and an Ultraflex stent in the longer term. However, oesophageal stent placement is not curative in cases of significant oesophageal perforation as it does not lead to lead to closure of a large defect.